The Effect Of Accounting Profit And Cash Profit On Cash Dividends In Pharmaceutic Al Companies Listed On IDX 2017-2020 - Silvia Rizqi Ardiani; Endang Kartini Panggiarti (Jurnal Ekonomi, Manajemen dan Akuntansi (JEKMA), 2022)
The purpose of this study is to analyze accounting earnings and cash earnings on cash dividends in pharmaceutical companies listed on the Indonesia Stock Exchange from 2017 to 2020. This study uses quantitative descriptive using secondary data. The data used are in the form of financial statements for the 2017-2020 period obtained on the Indonesia Stock Exchange website and the official websites of each company. The variables used are independent variables, namely accounting profit (X1) and cash income (X2), and the dependent variable is cash dividends (Y). Data analysis in this study uses panel data, which is a combination of time series data and cross data. Then hypothesis testing is done by using panel data regression model. The results of the analysis and hypothesis testing in this study in the form of accounting profits have no effect on cash dividends, cash earnings have an effect on cash dividends, and accounting profits have an effect on cash dividends.